(untitled) (IAHS Medical Journal, 2025)
Background: Ultrasonography is the most admissible method for gestational age estimation worldwide. The current study was aimed to determine the accuracy of fetal foot length and its correlation with femur length for fetal gestational age prediction in among Bangladeshi uncomplicated pregnant women of Chattogram district. Materials and methods: This cross-sectional observational study, conducted in Chittagong Medical College, Chattogram, included 200 uncomplicated pregnant women of 15th to 28th weeks of gestation. Fetal biometric parameters such as fetal foot length and femur length were measured by 2D ultrasonography. For statistical analysis Pearson’s correlation test and correlation-regression analysis was done and p-value was considered significant if it was <0.05 at 95% level of confidence. Results: Pearson’s correlation test showed that gestational age had strong positive and highly significant (p=0.000) correlation with both fetal foot length and femur length. The relation between gestational age and fetal foot length (r=0.984) was stronger than the relation between gestational age and femur length (r=0.979). Conclusion: This study revealed definiteness of fetal foot length measurement for ultrasonographic fetal gestational age appraisal. Fetal foot length might be considered as a new parameter apace with classical biometric parameters for meticulous pregnancy dating. IAHS Medical Journal Vol 7(2), December 2024; 14-18